2022
DOI: 10.1001/jamanetworkopen.2021.37277
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Fosfomycin for the Treatment of Multidrug-Resistant Escherichia coli Bacteremic Urinary Tract Infections

Abstract: This randomized clinical trial investigates noninferiority of fosfomycin vs ceftriaxone or meropenem in achieving clinical and microbiological cure among patients with urinary tract infections due to multidrug-resistant Escherichia coli .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 23 publications
1
35
0
5
Order By: Relevance
“…A recent open‐label RCT compared intravenous fosfomycin versus a β‐lactam (ceftriaxone or meropenem) for patients with BSI from urinary source due to MDR (mainly ESBL‐producing) E. coli . While clinical or microbiological failure was lower with fosfomycin than with the comparator (14.3% vs. 19.7%, respectively), the primary outcome of non‐inferiority was not met due to an increased rate of AE‐related discontinuations in the former group, mostly due to the occurrence of heart failure (which happened only in patients over 80 years and those with preexisting heart disease or renal failure) 118 . Although fosfomycin showed high efficacy, this trial exemplifies that patients to be treated with intravenous fosfomycin at doses of 4–6 g every 6–8 h should be properly selected.…”
Section: Therapeutic Options For Esbl‐e and Cre Infections In The Sot...mentioning
confidence: 95%
“…A recent open‐label RCT compared intravenous fosfomycin versus a β‐lactam (ceftriaxone or meropenem) for patients with BSI from urinary source due to MDR (mainly ESBL‐producing) E. coli . While clinical or microbiological failure was lower with fosfomycin than with the comparator (14.3% vs. 19.7%, respectively), the primary outcome of non‐inferiority was not met due to an increased rate of AE‐related discontinuations in the former group, mostly due to the occurrence of heart failure (which happened only in patients over 80 years and those with preexisting heart disease or renal failure) 118 . Although fosfomycin showed high efficacy, this trial exemplifies that patients to be treated with intravenous fosfomycin at doses of 4–6 g every 6–8 h should be properly selected.…”
Section: Therapeutic Options For Esbl‐e and Cre Infections In The Sot...mentioning
confidence: 95%
“…Eine spanische, randomisierte, kontrollierte Multicenterstudie untersuchte, ob bei Patient*innen mit bakteriämischer Escherichia-coli -Harnwegsinfektion der Cephalosporin- und Carbapenem-Verbrauch reduziert werden können. Es wurde geprüft, ob eine Therapie mit Fosfomycin (4-mal 4 g/Tag) anstatt eines 3.-Generations-Cephalosporins (Ceftriaxon 1 g/Tag) oder – bei Cephalosporin-Resistenz – Carbapenem (Meropenem 3‑mal 1 g/Tag) eingesetzt werden kann [ 25 ]. Patient*innen mit komplizierenden Faktoren wie septischem Schock, Prostatitis, Zustand nach Nierentransplantation und verzögerter Drainage bzw.…”
Section: Gibt Es Cephalosporin- Oder Carbapenem-sparende Alternativsu...unclassified
“…Additionally, the activity of tebipenem against selected strains within the tested collection expressing co-resistance to ciprofloxacin and trimethoprim/sulfamethoxazole was also assessed in order to ascertain the suitability of tebipenem as a potential alternative to these traditional oral options. Although there has been renewed interest in the use of fosfomycin for the treatment of bacteraemia due to MDR E. coli , 23 several studies have reported an increased likelihood of treatment failure with regard to K. pneumoniae and, consequently, caution in the use of fosfomycin for such infections. 24 , 25 …”
Section: Introductionmentioning
confidence: 99%